2021
DOI: 10.3390/healthcare9070780
|View full text |Cite
|
Sign up to set email alerts
|

Determining Factors Affecting the Acceptance of Medical Education eLearning Platforms during the COVID-19 Pandemic in the Philippines: UTAUT2 Approach

Abstract: eLearning has been the medium of delivery of medical educational institutions to address the scarcity of medical professionals during the COVID-19 pandemic. In this study, the Unified Theory of Acceptance and Use of Technology (UTAUT2) was extended to determine the factors affecting the acceptance of eLearning platforms to medical education in the Philippines during the COVID-19 pandemic. A total of 360 medical students voluntary participated and answered an online questionnaire that consisted of 40 questions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 37 publications
4
28
1
Order By: Relevance
“…Greater behavioral intention increases the likelihood of a desired behavior. In this context, increased behavior intention with increased learning values means that students that experience learning value are more likely to utilize digital education and learning platforms in a productive way [ 12 ]. Other studies have reported that an increased sense of time efficiency among medical students related to digital education have led to increased family time, better quality of sleep and increased opportunities for research [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Greater behavioral intention increases the likelihood of a desired behavior. In this context, increased behavior intention with increased learning values means that students that experience learning value are more likely to utilize digital education and learning platforms in a productive way [ 12 ]. Other studies have reported that an increased sense of time efficiency among medical students related to digital education have led to increased family time, better quality of sleep and increased opportunities for research [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Instructor characteristics are defined as qualities that makes a good instructor or teacher [ 16 ]. Qualities such as being able to fully utilize an eLearning platform and answering questions, are good instructor characteristics, and are found to increase behavioral intention in students in context of digital learning [ 12 ]. However, medical students in our study did request a higher degree of familiarization of technical aids from their teachers.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 126 respondents coming from different educational levels of one university in the Philippines was considered. Only two universities in the Philippines offer undergraduate to Doctor of Philosophy under IE-EMG, namely Mapua University and De La Salle University [71,72]. Due to the COVID-19 pandemic, purposive sampling from Mapua University was considered in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, SEM can analyze the most complex linkages between latent factors [46][47][48][49][50][51]. Because of this, SEM can be used for analyzing the factors on why the users use technology in the first place [52,53]. With this current pandemic, it is not a surprise that almost everyone will depend on the usage of technology, especially in the sector of education.…”
Section: Theoretical Contributionsmentioning
confidence: 99%